Urgensi Pengetahuan Masyarakat Berdaya Terhadap Pinjaman Online Ilegal - Shafira, Maya; Cemerlang, Aisyah Muda; Achmad, Deni; Zazili, Ahmad (FT Universitas Lampung, 2024)
More and more people are using online loans and stating that online loans are an alternative financial service that is easy to use, can save time and is in accordance with the needs of the community, but there are negative impacts, namely if the community does not understand the loan procedure, SOP from the related institution, the amount of interest applied and the legality of the online loan fintech. The purpose of this service is to focus more on the community who do not have sufficient knowledge regarding the dangers of online loans. The approach method used in this Community Service is through the lecture method in delivering the material, then at the end of the event a question and answer session is held. With this question and answer method, the community is given the opportunity to ask questions according to the theme or other relevant questions. The benefits of holding this activity in Mukti Jaya Village, Tanjung Raya District, Mesuji Regency are to realize better legal awareness in the community so that every member of the community realizes and appreciates the importance of knowledge about illegal online loans.